Polarization of Government and NGO Orientation towards Eco-Rural Tourism Development in Kerinci Region, Jambi Province, Indonesia - Occy Bonanza; Ricky Avenzora; Elly Malihah; Rachmad Hermawan (Universitas Negeri Semarang, 2023)
Rural is an area that should be conserved. Conservation in the sense that its development must be in accordance with the concepts and potentials that have been passed down from generation to generation. The success of rural area development is strongly influenced by the orientation of stakeholders, including the government and NGOs. The purpose of this study is to analyze the polarization of the government and NGOs orientation towards the development of eco-rural tourism in Kerinci Regency, Jambi Province. This study used an instrument in a closed questionnaire with a One Score One Indicator Scoring System assessment pattern, with aspects assessed including socio-cultural, conservation and environmental aspects, ethnic politics, economics, regional development, tourism, and landscape ecology in six villages. The polarization of government and NGO orientations is measured by perception, then analyzed using the Kruskal Wallis statistical test by quantitative and comparative descriptive methods. The results showed that the government and NGOs stated that the concept of eco-rural tourism was relevant to be built and developed in rural areas. The direction of polarization from the orientation of the government and NGOs shows the same direction, namely a positive direction and a strong polarization scale. This means that the government and NGOs have agreed to develop their rural areas into eco-rural tourism by meeting the indicators that have been formulated. The perception of the government and NGOs will strengthen the application of this concept. This study concludes that the government and NGOs have an excellent opportunity to create collaboration in developing rural areas in accordance with the concept of eco-rural tourism.